The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00339-015-9320-z
|View full text |Cite
|
Sign up to set email alerts
|

Laser wavelength effect on laser-induced photo-thermal sintering of silver nanoparticles

Abstract: This work is concerned with the laser wavelength effect on the electrical properties and surface morphology of laser-sintered nanoparticle thin films. Silver nanoparticle thin films spin-coated on soda lime glass substrates were irradiated with lasers of three different wavelengths (near ultraviolet 405 nm, green 514.5 nm, near infrared 817 nm) at varied laser intensities and scanning speeds. Scanning electron microscopy images and ex situ resistivity measurements show that the photo-thermal sintering alters s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 45 publications
0
44
0
2
Order By: Relevance
“…Note that there exists damage threshold for plastic substrates such as PI and PET. Due to the monochromaticity of lasers, wavelength is not an easily adjustable parameter in many cases, but the effect of laser wavelength in the sintering process has also been investigated for silver nanoparticles by utilizing three different (diode) lasers [18]. Paeng et al utilized three laser diodes at 405, 514.5, and 817 nm, whose optical penetration depths are 28.3, 43.5, and 171 nm, respectively, for the Ag nanoparticle film.…”
Section: Mechanismmentioning
confidence: 99%
“…Note that there exists damage threshold for plastic substrates such as PI and PET. Due to the monochromaticity of lasers, wavelength is not an easily adjustable parameter in many cases, but the effect of laser wavelength in the sintering process has also been investigated for silver nanoparticles by utilizing three different (diode) lasers [18]. Paeng et al utilized three laser diodes at 405, 514.5, and 817 nm, whose optical penetration depths are 28.3, 43.5, and 171 nm, respectively, for the Ag nanoparticle film.…”
Section: Mechanismmentioning
confidence: 99%
“…The modified optical settings are found to be advantageous for the creation of repetitive conducting patterns or areal sintering of the silver nanoparticle ink layer [145]. Yu et al [146][147][148][149] compared the effects of laser type, wavelength, and power on the electrical properties and surface morphologies of sintered nano thin film. The results showed that the picosecond pulsed laser did less damage to the substrate as compared with the nanosecond pulsed laser and continuous laser.…”
Section: Laser Sinteringmentioning
confidence: 99%
“…Promising results of laser sintering of metal nanoparticle inks have been reported by many authors, mostly with ink layers of thickness below one micron (i.e., <1,000 nm) [6][7][8][9][10][11]. Unlike inkjet printing which operates with larger droplets of low viscosity inks, the Aerosol JetÂź printed lines can have a much higher aspect ratio (with layer thickness typically of several microns as printed in a single pass) because of the effective inflight solvent removal with microdroplets of appropriately formulated inks [12].…”
Section: Introductionmentioning
confidence: 99%